Pengembangan Perangkat Lunak Program Inventarisasi Asset dengan Menggunakan PHP - Hanief Aditiawan; Mila Amelia; Safru Rozaky; Thoyyibah. T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Along with the development of internet technology, an asset inventory system began to be developed. Because it encourages the author to maintain the quality of asset data collection by developing Asset Inventory Program Software at the Tadika Puri Education Foundation using PHP. PHP is a web-based programming language where the system implemented is on the server side. PHP can be inserted between HTML language scripts and other server side language arenas, with that PHP will be executed directly on the server. While the browser will execute the web page through the server which will then receive the "finished result" in HTML form, while the PHP code itself will not be visible.